Costimulators expressed on human endothelial cells modulate antigen-dependent recruitment of circulating T lymphocytes - Manes, Thomas D.; Wang, Vivian; Pober, Jordan S. (Frontiers in Immunology, 2022)
Endothelial cells (ECs) can present antigens to circulating effector memory T cells (TEM) and to regulatory T cells (T regs), triggering antigen-specific extravasation at specific sites where foreign antigens are introduced, e.g. by infection or transplantation. We model human antigen-induced transendothelial migration (TEM) using presentation of superantigen by cultured human dermal microvascular (HDM)ECs to isolated resting human peripheral blood T cell subpopulations or to T effector cells activated in vitro. T cell receptor (TCR)-mediated cytokine synthesis, a common assay of T cell activation by antigen, is modulated by antigen-independent signals provided by various positive or negative costimulator proteins (the latter known as checkpoint inhibitors) expressed by antigen presenting cells, including ECs. We report here that some EC-expressed costimulators also modulate TCR-TEM, but effects differ between TEM and cytokine production and among some T cell types. Blocking EC LFA-3 interactions with TEM CD2 boosts TEM but reduces cytokine production. Blocking EC ICOS-L interactions with TEM CD28 (but not ICOS-L) reduces both responses but these involve distinct CD28-induced signals. Activated CD4+ T effector cells no longer undergo TCR-TEM. Engagement of T cell CD28 by EC ICOS-L increases TCR-TEM by activated CD8 effectors while engagement of OX40 promotes TCR-TEM by activated CD4 T regs. B7-H3 mostly affects TEM of resting TEM and some checkpoint inhibitors affect cytokine synthesis or TEM depending upon subtype. Our data suggest that blockade or mimicry of costimulators/checkpoint inhibitors in vivo, clinically used to modulate immune responses, may act in part by modulating T cell homing.